Innovate or fail: keys to think about a new institutionalization of learning in the 21st century school - Ricci, Cristina Rafaela (2021)
This essay is based on the following questions: what to do, so that what happens in the classrooms makes any sense? And, what to do today with the modern school? These questions take on value and urgency, not only in the context of the pandemic caused by the virus responsible for COVID-19, which has exposed the weaknesses and potential of societies, states, school and education systems but in addition, in the first decades of the XXI century, in the face of the exhaustion of the massive schooling typical of Modernism in the XIX and XX centuries. In the confinement and preventive isolation, mandatory or suggested in this pandemic, the outbreak has been experienced and evidenced behind the screens –as it usually happens in many classrooms– of complaints and claims from children, youth and adults, synthesized in the question: ‘what is this for?’, with regard to teaching practices and school content. The general objective of this essay is to provide conceptual elements that allow us to think about other school formats and the design of classrooms and classes in which learning and teaching take on new meaning for the student body and the construction of another pedagogical subject. From the historical perspective, regarding social psychology, and pedagogical, didactic and psycho-pedagogical psychology, the analysis presented allows to conclude that it is not a question of ‘breaking’ with the current school. However, based on what exists, it is necessary and possible to institute a synergistic movement of change-innovation whenever the value of teaching is preserved and another conception of learning is institutionalized.